Approaches of the decimal numbering system in the initial series - Silva, Mônica de Oliveira Pinheiro da; Pimenta, Maria Alzira de Almeida (Revista Hipótese, 2019)
This article presents partial results of a doctorial thesis, which goal is the teaching of Decimal Numeric System on 2nd year of basic school, applied to a government school. It was sought to identify how teachers work the subject, pedagogically. A qualitative approach was used, based on observation, and a field study was developed. Two main aspects were apointed about this learning-teaching relation: (1) teacher background to lead concepts absortion process, respecting students` cognitive maturity levels and (2) conflict between moving ahead with the planned contents or staying on the current content in order to guarantee a solid absortion.
Keywords: Decimal Numeric System; Learning; Didactic